Foundation's Preaching Strategy in Building Donor Loyalty: Case Study at Rabbunallah Surabaya Tahfidz and Orphanage - Fithriani, Ulya; Wailah, Carissa Shofwah; Novita, Ayu Farinda; Afrianto, Dimas; Ilham, Moh (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2024)
This study identifies and analyzes the Da’wa strategies the Rabbunallah Surabaya Foundation implemented to build donor loyalty. The research focuses on understanding how the foundation's da’wa approach influences the relationship between the foundation and its donors, encouraging long-term commitment to supporting its social activities. Using a Grounded Theory methodology, the study adopts a qualitative case study approach, gathering data through in-depth interviews with foundation managers, donors, and related parties and observing da’wa activities. Data analysis used open and axial coding to identify key categories related to Da’wa strategies and donor loyalty. The findings reveal that the foundation's da’wa strategy involves a combination of educational, emotional, and spiritual approaches, focusing on delivering messages of goodness and the importance of sustaining charitable efforts. This strategy fosters a personal and emotional bond between the foundation and its donors. Additionally, the foundation utilizes various communication platforms, such as social media and regular meetings, to maintain transparency and provide updates on program developments. Donor loyalty is built through involvement, trust, and the fulfillment of spiritual and social expectations. In conclusion, the da’wa strategies employed by the Rabbunallah Surabaya Foundation have proven effective in cultivating donor loyalty. Active involvement in da’wa activities that touch on spiritual and social aspects plays a key role in creating lasting relationships between the foundation and its donors. This study contributes to a deeper understanding of the dynamics between foundations and donors within Islamic da’wa.